A retrospective study of the mid-term efficacy of full-endoscopic annulus fibrosus suture following lumbar discectomy - Wang, Zhenfei; Huang, Sen; Xu, Long; Bu, Jinhui; Liu, Guangpu; Wang, Hui; Liang, Jun; Xia, Mengjiao; Chen, Tao; Ma, Chao; Dai, Kerong; Liu, Guangwang (Frontiers in Surgery, 2022)
Aims: Full-endoscopic discectomy is superior to open discectomy due to its faster recovery, short hospitalization time, lower blood loss volume, and lower infection rate. However, full-endoscopic discectomy is associated with a high risk of disc reherniation due to the poor mechanical strength of the annulus fibrosus after scar healing, propensity for the residual nucleus pulposus in the intervertebral disc to protrude into the spinal canal, and mechanical stimulation caused by the damaged annulus fibrosus. It is technically difficult to place a full-endoscopic annulus fibrosus suture. We designed an annulus fibrosus suture device with an anchoring wire rod that can be used to suture annulus defects under microendoscopy. The present study investigated the safety and feasibility of this technology. Results: The cohort comprised 82 patients, including 40 patients in the LD+AFS group and 42 in the LD group. The mean age was 39.7 years (range: 16–59 years). All operations were successfully completed without serious complications. Reherniation occurred in no patients in the LD+AFS group and three patients (7.14%) in the LD group. Postoperative lumbar MRI showed complete removal of the herniated disc and adequate nerve decompression in all patients. The VAS scores for lumbar and leg pain and ODI score were significantly improved postoperatively (p < 0.05). Lumbar MRI performed 1 year postoperatively showed that the modified Pfirrmann grade of disc degeneration was improved compared with preoperatively (p < 0.05). Conclusion: Compared with conventional lumbar discectomy, full-endoscopic annulus fibrosus suture following full-endoscopic lumbar discectomy is a safe and effective minimally invasive technique that reduces the LDH recurrence rate.